Type and non-type specimens of Aegla (Decapoda: Anomura: Aeglidae) housed in the Museo de La Plata, Argentina - César, Inés Irma (2010)
The present contribution deals with the type and non-type material of the species of Aegla (Decapoda: Anomura: Aeglidae) deposited in the Invertebrate Collection of Museo de La Plata, Argentina. One hundred and thirty-four lots are included, of which 10 lots are type specimens. The material examined includes 11 of the 13 species known from Argentina. Among the studied lots, those examined by Ringuelet (1948, 1960) and by Bond-Buckup & Buckup (1994) stand out. Also, several lots from different regions of Argentina were identified. Type specimens examined were compared with the original descriptions; photographs of the specimens are given in the present report. For each lot the following information is provided: georeferenced locality of collection, collector and collecting date, bibliographical references, category, number of collection according to the rules of the Museo de La Plata, label data (precise transcription), remarks and map of the locations.